Penerapan Akuntansi Manajemen dalam Meningkatkan Efisiensi Operasional Menggunakan Analisis ROA ( Return On Assets ) pada PT Astra Internasional Tbk - Akbar Juliansyah Firdaus; Muhammad Daffaa; Zacky Ramadhan; Abdul Rofiq Ode Laadjib (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study examines the role of management accounting in improving a company's operational efficiency through the analysis of Return on Assets (ROA) as a financial performance indicator. The main focus of this study is how the application of management accounting information can assist management in planning, controlling, and evaluating operational activities more effectively. The research method used is descriptive with a qualitative approach, utilizing secondary data obtained from the financial statements of PT Astra International Tbk. The results of the study indicate that the application of good management accounting is able to provide relevant information for management to increase productivity, reduce operational costs, and optimize the use of company assets. The ROA analysis shows that the increase in operational efficiency is in line with the effectiveness of the application of the management accounting system in the decision-making process. Thus, management accounting plays a strategic role as an internal control tool that contributes to the achievement of company goals in a sustainable manner.